Tell Shimshara. The Hassuna Period - Mortensen, Peder (1970)
With an Introduction by Harald Ingholt and Contributions by Anne-Tinne and Mogens Lonborg Friis, Colin Renfrew, Henrik Tauber and others; folding plate; 13ff.: on tablet discoveries and history of Shimshāra.